2023
DOI: 10.1088/1402-4896/ace1b2
|View full text |Cite
|
Sign up to set email alerts
|

Fractional order interdependent nonlinear chaotic spatiotemporal calcium and Aβ dynamics in a neuron cell

Abstract: The formation of β-amyloid (Aβ) and its accumulation depend on the calcium ([Ca2+]) signaling in neurons. The individual and independent dynamics of calcium and β-amyloid give very limited information about different cellular mechanisms. Some researchers have explored the interdependent system dynamics of integer-order calcium and β-amyloid, which provides some more crucial information on different regulatory and dysregulatory processes in neurons. However, these integer-order systems are not capable of genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…All the values of these parameters are given in Table 1. incorporating the equations (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). we obtain the proposed model,…”
Section: Role Of Voltage-gated Calcium Channelmentioning
confidence: 99%
See 1 more Smart Citation
“…All the values of these parameters are given in Table 1. incorporating the equations (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). we obtain the proposed model,…”
Section: Role Of Voltage-gated Calcium Channelmentioning
confidence: 99%
“…Naik modeled the Bazykin-Berezovskaya model for diffusion system [18]. Pawar and Pardasani have modeled the amyloid beta and calcium dynamics on cellular degeneration [19]. Y Jagtap and N. Adlakha have studied the calcium and IPR dynamics by using the finite volume method [20].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of age-wise transmission dynamics of COVID-19 patterns has been studied in the given literature [22,23]. However, the mathematical model to examine the impact of various physiological parameters that disturb nerve cells and invite neurodegenerative conditions has been studied in the given literature [24][25][26][27][28][29][30][31][32][33][34][35]. The co-dynamics of COVID-19 with diabetes [36], comorbidity [37], bacterial pneumonia [38], and tuberculosis [39] are proposed and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the occurrence of superdiffusive behavior is contingent upon the absence of equilibrium between birth and death processes in tumor cells [77]. The influences of memory and superdiffusion on the systems of calcium and Aβ and calcium and IP 3 were studied in neurons [78,79].…”
Section: Introductionmentioning
confidence: 99%